The Influence of Psychological Factors and Social Interaction on Impulse Buying in Social E-Commerce: A Systematic Literature Review - Iriyanti, Evi (Dinasti International Journal of Digital Business Management, 2025)
This study aims to analyze psychological and social factors, as well as the role of information quality and platform features, in triggering impulsive buying behavior in social e-commerce. The method employed is a systematic literature review, which identifies and analyzes findings from various relevant research articles. The main results indicate that psychological factors such as emotions, a sense of urgency, and low self-control have a significant influence on impulse buying. In addition, social influence arising from interactions with influencers or celebrities has been shown to increase consumers’ impulsive purchase decisions. Clear and comprehensive information quality, along with platform features such as product recommendations and rating systems, play an important role in stimulating impulse buying. This study concludes that impulse buying in social e-commerce is influenced by the interaction of psychological factors, social factors, and platform features. These findings contribute to a deeper understanding of consumer behavior in social e-commerce and can be used to design more effective marketing strategies.